การบูรณาการระบบบริหารความเสี่ยงกับการประเมินประสิทธิภาพแบบดุลยภาพ กรณีศึกษา : อุตสาหกรรมบริการประเภทธุรกิจประกันชีวิต - ปฐมพงศ์ เอี่ยมบุญฤทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objectives of this thesis is to build the integration system of risk management and balanced Scorecard. The integration system is applied in A company. Concepts of integration system of risk management and balanced scorecard by studying balanced scorecard theory found that the weakness of balanced scorecard lack perspective of risk management The process of building the integration system begin with four factors; vision mission objectives and balanced scorecard A company lack balance in all four perspectives Second, The building BSC cover three level; executive department and personnel. Third, the building RMBSC WORKSHEET in all three levels in order to illustrate goal and risk. Fourth, risk identification risk analysis and risk evaluation found that A company has twenty two extreme level risk which is divide into three sections. There was four risk, fifth teen risk, and three risk in executive department and personnel level respectively.The result is integration system which help reduce likelihood of risk unachieved objectives under four perspectives get 64%. Then evaluation of integration system compare between before and after implementation in A company found that increase 39.39%.